2008
DOI: 10.1016/j.dam.2007.05.056
|View full text |Cite
|
Sign up to set email alerts
|

An all-substrings common subsequence algorithm

Abstract: Given two strings A and B of lengths n a and n b , n a n b , respectively, the all-substrings longest common subsequence (ALCS) problem obtains, for every substring B of B, the length of the longest string that is a subsequence of both A and B . The ALCS problem has many applications, such as finding approximate tandem repeats in strings, solving the circular alignment of two strings and finding the alignment of one string with several others that have a common substring. We present an algorithm to prepare the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Based on the ideas of Schmidt [101], Alves et al [7] gave an algorithm for the string-substring LCS problem that runs in time O(mn), which therefore extends the functionality of the standard dynamic programming algorithm, while matching its asymptotic running time. In the course of the computation, the string-substring LCS problem is solved for all prefixes of a against all prefixes of b.…”
Section: The Seaweed Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the ideas of Schmidt [101], Alves et al [7] gave an algorithm for the string-substring LCS problem that runs in time O(mn), which therefore extends the functionality of the standard dynamic programming algorithm, while matching its asymptotic running time. In the course of the computation, the string-substring LCS problem is solved for all prefixes of a against all prefixes of b.…”
Section: The Seaweed Algorithmmentioning
confidence: 99%
“…The LCS score of string a against substring b 4 : 11 = "cabcaba" is 5; this score is realised by a common subsequence "abcba". This example, which will serve as a running example for this chapter, is borrowed from Alves et al [7].…”
Section: Examplementioning
confidence: 99%
“…In the same paper, Schmidt showed that IGAPS can be solved in O(Cn 2 ) time. An O(n 2 ) algorithm based on a similar approach for the BGAPS problem was also given by Alves et al [1] and Tiskin [23]. Tiskin [22, p. 60] gave an O(n 2 (log log n/ log n) 2 ) time algorithm for a special case of BGAPS, in which the grid graph corresponds to an LCS problem on two strings.…”
Section: Introductionmentioning
confidence: 99%
“…It has since been studied in several additional papers [1,2,7,[11][12][13][14][15][21][22][23]. Schmidt [21] showed that the GAPS problem can be solved in O(n 2 log n) time.…”
Section: Introductionmentioning
confidence: 99%